A new large-sized lepetid limpet from the abyssal northwestern Pacific is the deepest known patellogastropod - Chong Chen; Miwako Tsuda; Yoshiyuki Ishitani (Zoosystematics and Evolution)
True limpets in the gastropod subclass Patellogastropoda are familiar members of shallow-water rocky environments but are much rarer in the deep, with just three families adapted to bathyal depths or more. Of these, Lepetidae is the only one found on ambient seafloor habitats, and Bathylepeta is a very deep genus known from two species off Chile and Antarctica. Here, we report a giant Bathylepeta up to a shell length of 40.5 mm from 5922 m deep in the northwestern Pacific and name it Bathylepeta wadatsumi sp. nov. Phylogenetic reconstruction using the mitochondrial cytochrome c oxidase subunit I (COI) gene supports the placement of this new species in Bathylepeta. Our new species is most similar to B. linseae from the Weddell Sea but can be distinguished by its much more developed second lateral and marginal teeth, as well as a larger size. Bathylepeta wadatsumi sp. nov. also has slightly imbricating radular basal plates, a feature previously unknown from this genus; we therefore emend the genus diagnosis. Our finding not only extends the distribution of this enigmatic limpet genus to Japan but also marks the deepest bathymetric record for the entire Patellogastropoda.